1996
DOI: 10.3109/00365549609027145
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Rate and Risk Factors for HCV Seroconversion Among Injecting Drug Users in an Area with Low HIV Seroprevalence

Abstract: We conducted a study on injecting drug users attending one of 3 drug treatment centres in Naples, to estimate HIV and hepatitis C virus (HCV) incidence rates and to identify risk factors for seroconversion. Incidence rates were estimated using as denominator the person-time of follow-up of participants who were negative for both HIV and HCV at enrollment and who were retested within 6-12 months. Information on risk factors was collected using a standardized questionnaire. A nested case-control analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 13 publications
4
70
1
Order By: Relevance
“…4,8,10,11 At the 2 sites in our study, the HCV infection prevalence was lower than was reported in these studies, and we found a longer time of injecting (>6 years) before reaching a peak prevalence of infection. Additionally, our reported prevalence was lower than the prevalence reported in young injection drug users in Baltimore.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…4,8,10,11 At the 2 sites in our study, the HCV infection prevalence was lower than was reported in these studies, and we found a longer time of injecting (>6 years) before reaching a peak prevalence of infection. Additionally, our reported prevalence was lower than the prevalence reported in young injection drug users in Baltimore.…”
Section: Discussioncontrasting
confidence: 74%
“…4,[7][8][9] However, we did not find direct syringe sharing, which is an established risk factor for HCV infection among injection drug users, [8][9][10][11] to be associated with prevalent HCV infection. Nevertheless, several correlates of HCV infection in our sample may have served as markers for syringe sharing.…”
Section: Discussionmentioning
confidence: 91%
“…In total, we included 21 published studies 14,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and seven unpublished studies [33][34][35][36][37]59,60 comprising 1827 HCV incident infections and 8789.7 person-years of follow-up. Overall HCV infection incidence ranged between 0.09 and 42 cases per 100 person-years across the studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Twenty-one of the included studies reported the impact of OST, 14,20,39,40,[45][46][47]49,[51][52][53]55,57,58 including seven unpublished estimates. [33][34][35][36][37]59,60 Seventeen studies reported the impact of NSPs, 14,20,[41][42][43][44]47,48,50,54,56,58 including five unpublished sources, [33][34][35]59,60 and four reported combined measures of NSPs with OST, 14,33,44,47 including one unpublished data source.…”
Section: Type Of Interventionsmentioning
confidence: 99%
See 1 more Smart Citation